Perovskite solar cells: progress and advancements - Elumalai, Naveen Kumar; Mahmud, M.; Wang, D.; Uddin, A. (M D P I AG, 2016)
Organic–inorganic hybrid perovskite solar cells (PSCs) have emerged as a new class of optoelectronic semiconductors that revolutionized the photovoltaic research in the recent years. The perovskite solar cells present numerous advantages include unique electronic structure, bandgap tunability, superior charge transport properties, facile processing, and low cost. Perovskite solar cells have demonstrated unprecedented progress in efficiency and its architecture evolved over the period of the last 5–6 years, achieving a high power conversion efficiency of about 22% in 2016, serving as a promising candidate with the potential to replace the existing commercial PV technologies. This review discusses the progress of perovskite solar cells focusing on aspects such as superior electronic properties and unique features of halide perovskite materials compared to that of conventional light absorbing semiconductors. The review also presents a brief overview of device architectures, fabrication methods, and interface engineering of perovskite solar cells. The last part of the review elaborates on the major challenges such as hysteresis and stability issues in perovskite solar cells that serve as a bottleneck for successful commercialization of this promising PV technology.